The polymorphism rs6918289 located in the downstream region of the TREM2 gene is associated with TNF-α levels and IMT-F - Vesna Gorenjak (Nature Portfolio, 2018)
Abstract Triggering receptor expressed on myeloid cells 2 (TREM2) is known for its anti-inflammatory properties during the immune response, and influences negatively on TNF-α expression levels. Genetic epidemiology studies have identified polymorphisms located in the TREM2 gene associated with neurodegenerative and chronic inflammatory diseases. TREM2 levels have been observed to affect plasma levels of TNF-α and plaque stability in symptomatic and asymptomatic patients with carotid stenosis. In this study, we investigated polymorphisms located in the TREM2 gene region and association with TNF-α levels and the intima media thickness of the femoral artery. The discovery population from the STANISLAS Family Study comprised of 809 individuals, whereas the replication population utilized an independent cohort of French origin (n = 916). Our results suggest that the minor allele (T) of SNP rs6918289 is positively associated with elevated plasma levels of TNF-α in discovery and replication populations (P = 0.0026, SE = 0.04 and P = 0.023, SE = 0.09, respectively), including femoral artery thickness in the discovery cohort (P = 0.026, SE = 0.009). Results indicate that rs6918289 may be considered as a risk factor for inflammatory diseases and could be used in stratified medicine with patients diagnosed with chronic inflammatory-related conditions, such as atherosclerosis.